Land use patterns and influences of protected areas on mangroves of the eastern tropical Pacific. (November 2018) - López-Angarita, Juliana; Tilley, Alexander; Hawkins, Julie P.; Pedraza, Carlos; Roberts, Callum M.
Abstract: Mangroves are one of the most productive ecosystems in the world, sustaining millions of coastal livelihoods. However, their area of occurrence has been greatly reduced over the last century. In this study, we identify potential drivers of land use and land cover change adjacent to mangroves on the Pacific shorelines of Colombia, Panama and Costa Rica. We also evaluate the effectiveness of protected areas at halting mangrove deforestation between 2000 and 2012. Across all countries, agriculture was the most dominant land use type adjacent to mangroves, inside and outside protected areas. Results show that a combined total of 564 ha were lost, representing an average loss rate of only 0.02% per year. 75% of the total mangrove loss occurred in locations outside protected areas, with only 138 ha cleared from inside protected areas. Results suggest current conservation policies for mangrove protection in the study countries are effective at reducing deforestation and set a positive example for regions where mangroves are in decline. Highlights: We identified land use around mangroves in 3 countries of the Eastern Tropical Pacific. Across all countries, the dominant land use adjacent to mangroves was agriculture. Mangrove deforestation slowed between 2000 and 2012 compared to the 20th century. 75% of mangrove loss occurred outside protected areas across all countries. Conservation policies have reduced mangrove deforestation rate in the region.